AN EVALUATION OF THE GOOD BEHAVIOR GAME IN KINDERGARTEN CLASSROOMS - Donaldson, Jeanne M (The Society for the Experimental Analysis of Behavior, 2011)
The good behavior game (GBG) is a classwide group contingency that involves dividing the class into two teams, creating simple rules, and arranging contingencies for breaking or following those rules. Five kindergarten teachers and classrooms participated in this evaluation of the GBG. Disruptive behavior markedly decreased in all five classrooms as a result of the intervention. This study extends the GBG literature by systematically replicating the effects of the GBG with the youngest group of students to date.